Effects of Oxytocin on Heart Rate and Blood Pressure During Cesarean Section Under Spinal Anaesthesia - Faryal Knawal, Tahreem Hassan, Muhammad Umar Abbas, Wajeeh Ur Rehamn, Fakhra Fakhr, Attaullah Khan Niazi (Pakistan Journal of Medical & Health Sciences, 2022)
Introduction: Noninvasive blood pressure and heart rate have typically been used to assess maternal haemodynamic changes after Caesarean section under spinal anaesthesia. To avoid a postpartum haemorrhage in women who have Caesarean Sections, oxytocin is the first-line uterotonic treatment (PPH). Aim: The purpose of this study is to determine the influence of oxytocin on hemodynamic parameters like as heart rate (HR) and blood pressure (BP) after caesarean surgery. Material and Methods: This study included 121 pregnant women aged 18 to 36 years old with an ASA grade I physical status and a term pregnancy (37 weeks or more) that underwent an elective caesarean delivery under spinal anaesthesia. The study design of this research was Cross-sectional. This research lasted six months (January 2021 to June 2021). This study was conducted at Obstetrics and Gynecology Operation theatre of Shalamar Hospital, Lahore. Hemodynamic parameters were measured non-invasively and compared the results before given the drug (oxytocin) considers as a baseline, then immediately after given the drug, after 1 minute and after 5 minutes of drug given. Results: The effects of oxytocin on hemodynamic parameters in C section patients under spinal anaesthesia were studied by the researcher. The purpose of this study was to assess the effects of oxytocin on hemodynamic parameters from baseline to after 5 mints of therapy. A total sample size of 121 women received oxytocin and their blood pressure and heart rate were monitored at after the dose given, after 1 mint and then after 5minutes. The patients included in present study were from mainly two age groups: one age group was 18-26 years and other age group was 27-36 years. The frequency and percentages of different age group as 71 (58.7 %) patients were from age group of 18-26 years and 50 (41.3%) patients were from 27-36 years. The mean HR at baseline, after given the dose, at after 1and 5 minutes was (88.66±8.816), (92.14±9.678), (109.74±18.01) and (95.90±8.646) respectively; however difference was statistically significant. The mean systolic blood pressure (SBP) at baseline was (112.82±12.08) and changed after given the dose, at 1 and 5 minutes as (112.72±11.17), (101.98±12.98), (111.89±12.55) respectively. Also the mean diastolic blood pressure (DBP) at baseline was 68.04±11.57 and decreased after given the drug andat1minutes to 67.74±12.31 and 58.95±9.291 respectively but returned to 67.26±9.295 at 5 minutes. To summarise, the differences in hemodynamic measures from baseline to 5 minutes after oxytocin delivery were statistically significant (p value; 0.05). Keywords: Spinal anaesthesia, Blood Pressure, Heart rate, Cardiac output, Cesarean section, Oxytocin, Haemodynamics, Uterus, Mean Arterial Pressure.